Immunohistochemistry in intrahepatic cholangiocarcinoma: histological subtyping and drug selection - Wang, Han; He, Miao-Xia; Cong, Wen-Ming; Dong, Hui (Frontiers in Oncology, 2025)
IntroductionSince the release of the World Health Organization (WHO) Classification of Tumours-Digestive System Tumours in 2019, the pathology of intrahepatic cholangiocarcinoma (iCCA) has entered an era of integrated diagnosis, encompassing gross classification, histological subtyping, as well as drug molecular target screening. Substantial evidence indicates that the histological subtypes of iCCA are significantly associated with the detection frequency of molecular targets relevant to the targeted therapy and immunotherapy. Through rational immunohistochemistry profiling, patients with iCCA can be precisely diagnosed and individually managed.MethodsA thorough literature search was conducted using terms pertinent to the pathological diagnosis, histological subtyping, targeted therapy, and immunotherapy of iCCA. The content related to immunohistochemistry was summarized.ResultsIn the first part, we summarize the immunohistochemical markers for the histological subtype of iCCA (e.g., large duct type iCCA, small duct type iCCA), with a particular emphasis on their percentage of positive cases, expression location, and association with prognosis. Subsequently, a summary of the immunohistochemical markers for targeted therapy and immunotherapy of iCCA is performed, focusing on the consistency between immunohistochemistry and molecular detection, optimal clone, and prognostic significance.ConclusionsThis review summarizes the critical role of immunohistochemistry in the pathological diagnosis of iCCA. It is noted that any diagnosis must be made by integrating comprehensive information. A pathological diagnosis merely based on immunohistochemical results is unreasonable. The development of subtype-specific and drug-targeted antibodies holds promise for refining iCCA precise diagnosis and therapeutic stratification.